ENSAYO DE CLASIFICACION MORFOLOGICA DE LOS SILICOFITOLITOS (Ameghiniana, 2013)
In the last years many reseach workers have recognized the importance of the study of silicophytoliths. Botanists, Geologists and Edaphologists have studied their chemical composition, physical properties and perdurability, so much as their role in sediments and soils. Nevertheless, up to here, there is not an identification guide for silicophytoliths in sediments, in which they appear as single clastic particles.Thinking that there is a lot of available information, the author has made this design of morphologic classification, with all the known types of phytoliths, identified in Gramineae, Cyperaceae, Podostemaceae, and other families unknown under this aspect. The classification is based on sizes and shapes. The first condition discerns two initial morphogroups: microsilicophytoliths and macrosilicophytoliths. In both groups (or morphogroups) it was possible to include all the known forms, grouped in morphotribes. Whenever it has been possible, the species, genera or family in which the corresponding varying was found, has been mentioned.